AB1096 Overactive lifestyle in patients with fibromyalgia as a core feature of bipolar spectrum disorder. (23rd January 2014) - Alciati, A.; Sarzi-Puttini, P.; Batticciotto, A.; Sgiarovello, P.; Atzeni, F.; Angst, J.
Abstract : Background: Fibromyalgia syndrome (FMS) is a diffuse musculoskeletal pain disorder, accompanied by tenderness on examination at specific anatomic sites known as tender points (TP), fatigue and non-restorative sleep. Objectives: We tested the hypothesis that the premorbid overactivity previously described in subjects with chronic fatigue and pain is a core feature of the manic/hypomanic symptoms characterizing bipolar spectrum disorders. Methods: 110 consecutive patients with fibromyalgia were assessed for bipolar spectrum disorders using two approaches. The first was based on a version of the DSM-IV SCID-CV interview modified to improve the detection of bipolar spectrum disorders, the second on the hypomania symptom checklist HCL-32, which adopts a dimensional perspective of the manic/hypomanic component of mood by including sub-syndromal hypomania. Results: The total sample included 110 patients (8 males and 102 females) with a mean age of 46.12±12.1 years). All patients were of Caucasian ethnicity and had a mean educational level of 11.6±3.37 years. The patients reported having had their first fibromyalgia symptoms an average of 10.8±9.8years before our psychiatric examination, but the time to diagnosis was 7.9±8.6 years. The modified SCID-CV diagnosed high rates of bipolar spectrum disorder in patients with fibromyalgia (86.3%). Of those, 63 subjects (67.7%) had a major bipolar spectrum disorder, namely bipolar II disorder and 32 (32.3%) a minor bipolar spectrum disorder, i.e. minor bipolar disorder and pure hypomania. Patients with fibromyalgia plus a major bipolar spectrum diagnosis did not differ from those with minor spectrum disorders in their demographic and clinical aspects. Hypomanic symptom counts on the HCL-32 confirmed high estimates of the bipolar spectrum, with 79% of subjects scoring 14 (threshold for hypomania) or above. No statistically significant differencesbetween the percentage of major bipolar spectrum and minor bipolar spectrum patients endorsing the individual items of the HCL-32 were found. Conclusions: Overactivity reported in previous studies may be considered a core feature of hypomanic symptoms or syndromes associated with bipolar spectrum disorders. Major and minor bipolar spectrum disorders are not associated with differences in demographic or clinical characteristics, in accordance with the growing body of studies showing that sub-threshold bipolar spectrum syndromes have relevant clinical severity and functional impairment. References: Van Houdenhove B, et al. Premorbid overactive lifestyle and stress-related pain/fatigue syndromes. J. Psychosom. Res. 2005; 58: 389-90. Angst J, et al. The HCL-32: towards a self-assessment tool for hypomanic symptoms in outpatients. J. Affect. Disord. 2005; 88:217-33. Disclosure of Interest: None Declared